Les Français de Valence : notes sur l’origine, le nombre et l’activité des migrants au xvie siècle - María Teresa Pérez Villalba (Les Cahiers de Framespa)
As part of the collective work conducted on trans-Pyrenean migrations from the Middle Ages to the Modern era, this contribution means to introduce some of the features of French emigration to the city of Valencia throughout the 16th century. Thereby, and from the analysis of two main sources, the article will show how conclusions with regard to some issues as migrants’ origins, their numbers, or their socio-professional status can reveal interesting nuances. Finally, the article will broach the influence that the group of the great French traders had on the city’s economy.